A phase-contrast-imaging core fluctuation diagnostic and first-principles turbulence modeling for JT-60SA. (15th September 2021) - Coda, S.; Iantchenko, A.; Brunner, S.; Toussaint, M.; Tanaka, K.
Abstract: A core fluctuation diagnostic based on the phase-contrast imaging (PCI) technique has been designed for the JT-60SA tokamak, with the assistance of a synthetic diagnostic coupled to a gyrokinetic code. Using a tangentially viewing geometry, this system would be able to resolve small-scale microturbulence as well as macroscopic fluctuations, with good spatial and temporal resolution, throughout the plasma cross-section and in all plasma regimes. The spatial resolution will be optimal (<5% of the minor radius) in the pedestal region and near the magnetic axis. The accessible wave-number range will cover the main ion-scale instabilities predicted to be at play, and optionally also the electron-scale ones. The new superconducting tokamak JT-60SA, which is due to begin operating in 2021, will be the largest tokamak ever built and the most significant intermediate step in magnetic-confinement fusion before the inception of ITER operations. Turbulence is the primary cause of anomalous transport, one of the primary limiting factors in controlled nuclear fusion. Understanding and possibly controlling turbulence thus remain paramount to the fusion quest, and JT-60SA offers the possibility of performing such studies for the first time in a true reactor-relevant environment, providing also a unique opportunity for code validation. This proposal is supported by a direct modeling effort, employing the gyrokinetic code gene and a PCI synthetic diagnostic. Linear and nonlinear flux-tube simulations have been performed for a typical high-performance scenario, to identify the spectral and spatial areas of interest and illustrate the potential for fruitful theory-experiment comparison. While only electrostatic simulations could be carried to full completion with the computing resources deployed for this study, the work has highlighted the importance of including electromagnetic effects for proper comparisons.